MOOCs in language materials development course: Internationalizing the EFL curriculum and developing students' global competences - Yuliati, Yuliati; Istiadi, Nabila Yumna; Buana, Lang; Yi Xe, Wirawati Ngui (English Education Department, Universitas Islam Indonesia, 2025)
In the era of globalized education, integrating international perspectives into higher education curricula has become extremely important to equip students with the skills, knowledge, and cultural competencies required in a globally connected world. This study explores the strategic development and implementation of Massive Open Online Courses (MOOC) as a tool to internationalize the curriculum in Language Materials Development classrooms. Drawing on interdisciplinary frameworks from curriculum studies, educational technology, and applied linguistics, the study investigates how MOOCs can serve as content delivery platforms and as pedagogical spaces that foster intercultural competence, digital literacy, and learner autonomy. The research employs a qualitative case study approach, examining the design process, instructional integration, and learner engagement of MOOCs. Findings reveal that MOOCs, when thoughtfully contextualized, promote collaborative learning, expose students to diverse linguistic and cultural resources, and support the development of globally relevant language materials. However, access, localization, and instructional design challenges also emerge, highlighting the need for adaptive strategies in MOOC implementation. The paper concludes by offering practical guidelines for integrating MOOCs into English language education curricula and underscores their potential to transform local classrooms into globally networked learning environments.